The Criticism of the Characterization of Sarah before Hajar and Immigration to Hijaz - Maryam Rastegar; Ali Pirhadi; Waliyollah Naqipourfar (آموزه‌های قرآنی, 2022)
One of the most important milestones in history is the immigration of hazrat Hajar (Arabic: هاجر) and Ismail (Arabic: إسماعیل) to the land with no water and vegetation “Hijaz” that it leaded to the establishment the divine and security shrine and city and reconstruction of Ka'aba. The justification of this immigration for such a vice like jealousy and ascribing it to Sarah (Arabic: سارة) is questionable that it is crucial to study the issue for being a famous story, its effect and propagation in sources, the artistic works and media. The following research with analytic-descriptive method is going to study this issue that in spite of the righteous attributes of Sarah in the holy Quran, her haughtiness under the effect of the claimed jealousy has opposition and being contradicting; therefore, it is vital to analyze this story in the holy Quran, history, hadith and ethics from all aspects and comparatively. In this paper after the functional and conceptual explanation of jealousy and comparative study of the texts, with centralizing on the description of the holy Quran as a valid criterion on the description of the story characteristics and criticism and examination of the holy Quran via Quran of the reports; it seems that such exegesis has not been in compatible with (harmony) the Quranic and it is not righteous to be propagated.